Skim coconut milk processing by thermal- and ultrasonic-thermal pasteurization - Ong, Lu Ki; Sutikno, Kevin Hosea; Jodie, Kennita Alvina; Riadi, Lieke (Jurnal Rekayasa Proses, 2023)
The coconut industry in Indonesia is significant for national income, with the potential for value-added products that could enhance the industry’s expansion. Skim coconut milk, a by-product of virgin coconut oil production, is a healthy substitute for dairy milk that can be consumed by people with lactose intolerance. The low-fat and high-protein content of skim coconut milk makes it a healthier alternative to regular coconut milk and cow milk. This study compares ultrasonic-assisted pasteurization of skim coconut milk to conventional pasteurization technique in terms of contamination reduction efficacy and energy efficiency with minimum product characteristic change. The process consisted of thawing frozen skim coconut milk, homogenization of liquid skim coconut milk and pasteurization in a shaking water bath or ultrasonic bath. Total cell counting was conducted, D-value and z-value were estimated to measure the effectiveness of pasteurization in reducing the number of harmful microorganisms in skim coconut milk. The study found that ultrasonic-assisted pasteurization reduced the number of microorganisms more effectively than conventional pasteurization with a lower energy consumption. The study showed the removal efficiency of ultrasonic-assisted pasteurization and conventional pasteurization at 70°C and 15 minutes were 28.74% and 12.33%, respectively. At that condition, energy consumption for every microbial cell being removed was approximately 3 times lower in ultrasonic-assisted pasteurization than the conventional one (0.13 kWh vs. 0.36 kWh). Skim coconut milk processed by ultrasonic-assisted pasteurization at 75°C for 15 minutes featured homogeneous white liquid with shelf time of 11.2 h, which was 2.65 times longer than the unprocessed coconut skim milk. The research suggests that ultrasonic-assisted pasteurization can be a feasible and sustainable processing technology for skim coconut milk, with potential commercial value for small companies and farmers in Indonesia.